PERANCANGAN SISTEM PAKAR DIAGNOSA PENYAKIT KEHAMILAN BERBASIS WEB - Ari Abdillah; Nurajijah Nurajijah; Imam Nawawi (Jurnal Techno Nusa Mandiri, 2018)
One of the problems faced by pregnant women is lack of obstetric and antenatal care in pregnancy. Currently also computer technology hasevolved as a data processing tool and producing information. An expert system is one solution to bring obstetric and antenatal care for pregnant women to diagnose the illness. In the application of this expert system using the forward chaining method which can diagnose the 13 types of diseases that are often experienced by pregnant women are : Hiperemesis Gravidarum Tingkat 1, Hiperemesis Gravidarum Tingkat 2, Hiperemesis Gravidarum Tingkat 3, Kehamilan Ektopik Terganggu (KET), Mola Hidatidosa, Plasenta Previa, Solutio Plasenta Ringan, Solutio Plasenta Sedang, Solutio Plasenta Berat, Preeklampsia Ringan, Preeklampsia Berat, Eklampsia dan Abortus. The system can helpwomen receive the diagnosis of diseases associated pregnancy health with rapid and relatively inexpensive, and get a solution to the disease byobserving symptoms perceived. With this web-based system, the system user can do it anywhere and anytime.